Customizing Pore System in a Microporous Metal–Organic Framework for Efficient C2H2 Separation from CO2 and C2H4 - Qiang Zhang; Guan-Nan Han; Xin Lian; Shan-Qing Yang; Tong-Liang Hu (Molecules, 2022)
Selective-adsorption separation is an energy-efficient technology for the capture of acetylene (C2H2) from carbon dioxide (CO2) and ethylene (C2H4). However, it remains a critical challenge to effectively recognize C2H2 among CO2 and C2H4, owing to their analogous molecule sizes and physical properties. Herein, we report a new microporous metal–organic framework (NUM-14) possessing a carefully tailored pore system containing moderate pore size and nitro-functionalized channel surface for efficient separation of C2H2 from CO2 and C2H4. The activated NUM-14 (namely NUM-14a) exhibits sufficient pore space to acquire excellent C2H2 loading capacity (4.44 mmol g−1) under ambient conditions. In addition, it possesses dense nitro groups, acting as hydrogen bond acceptors, to selectively identify C2H2 molecules rather than CO2 and C2H4. The breakthrough experiments demonstrate the good actual separation ability of NUM-14a for C2H2/CO2 and C2H2/C2H4 mixtures. Furthermore, Grand Canonical Monte Carlo simulations indicate that the pore surface of the NUM-14a has a stronger affinity to preferentially bind C2H2 over CO2 and C2H4 via stronger C-H···O hydrogen bond interactions. This article provides some insights into customizing pore systems with desirable pore sizes and modifying groups in terms of MOF materials toward the capture of C2H2 from CO2 and C2H4 to promote the development of more MOF materials with excellent properties for gas adsorption and separation.